Gastrointestinal Stromal Tumor: May Mimic Adnexal Mass. - Karaca, Nilay; Akpak, Yasam Kemal; Tatar, Zeynep; Batmaz, Gonca; Erken, Aslihan (My University, 2015)
Gastrointestinal stromal tumors (GISTs) are rare tumor of the gastrointestinal tract. GISTs occur in the entire gastrointestinal tract and may also arise from the retroperitoneum, omentum and mesenteries. They are originated from gastrointestinal pacemaker cells (Cajal's interstitial cells) and range from benign tumors to sarcomas at all sites of occurrence. Diagnosis of GIST could be deceptive because of their similarity in appearance to gynecological neoplasms. We would like to present a case of a woman with GIST in the small intestine giving a imprint of an adnexal mass was diagnosed correctly during surgery. The diagnosis and treatment of GIST has been reformed over the past years. It is crucial to separate GISTs from possible misdiagnosis because their prognosis and treatment could be unlike clearly. The purpose of this case is to evaluate this rarely seen clinical entity, and thus, make some contribution to the literature.